Dopamine Receptor Blockade Attenuates Purinergic P2X4 Receptor-Mediated Prepulse Inhibition Deficits and Underlying Molecular Mechanisms - Khoja, Sheraz; Asatryan, Liana; Jakowec, Michael W.; Davies, Daryl L. (Frontiers in Cellular Neuroscience, 2019)
Sensorimotor gating refers to the ability to filter incoming sensory information in a stimulus-laden environment and disruption of this physiological process has been documented in psychiatric disorders characterized by cognitive aberrations. Lack of efficacious medications to treat sensorimotor gating perturbations signifies the need to elucidate molecular mechanisms for therapeutic intervention. Notably, we recently reported a role for purinergic P2X4 receptors (P2X4Rs) in regulation of sensorimotor gating using prepulse inhibition (PPI) of acoustic startle reflex. P2X4Rs are ion channels gated by adenosine-5’-triphosphate (ATP). Ivermectin (IVM) induced PPI deficits in C57BL/6J mice in a P2X4R-specific manner. Furthermore, mice deficient in P2X4Rs [P2X4R knockout (KO)] exhibited PPI deficits that were alleviated by dopamine (DA) receptor antagonists demonstrating an interaction between P2X4Rs and DA receptors in PPI regulation. On the basis of these findings, we hypothesized that increased DA neurotransmission underlies IVM-mediated PPI deficits. To test this hypothesis, we measured the effects of D1 and D2 receptor antagonists, SCH 23390 and raclopride respectively and D1 agonist, SKF 82958 on IVM-mediated PPI deficits. To gain mechanistic insights, we investigated the interaction between IVM and dopaminergic drugs on signaling molecules linked to PPI regulation in the ventral striatum. SCH 23390 significantly attenuated the PPI disruptive effects of IVM to a much greater degree than that of raclopride. SKF 82958 failed to potentiate IVM-mediated PPI disruption. At the molecular level, modulation of D1 receptors altered IVM’s effects on dopamine and cyclic-AMP regulated phosphoprotein of 32kDa (DARPP-32) phosphorylation. IVM interacted with the DA receptors antagonists in regulation Ca2+/calmodulin kinase IIα (CaMKIIα) phosphorylation, but not its downstream target, neuronal nitric oxide synthase (nNOS). Current findings suggest an involvement for D1 and D2 receptors in IVM-mediated PPI disruption via modulation of DARPP-32. Taken together, the findings suggest that stimulation of P2X4Rs can lead to DA hyperactivity and disruption of information processing, implicating P2X4Rs as a novel drug target for treatment of psychiatric disorders characterized by sensorimotor gating deficits.